Love waves in a nonlocal elastic media with voids. (April 2019) - Kaur, Gurwinderpal; Singh, Dilbag; Tomar, SK
The propagation of Love-type waves in a nonlocal elastic layer with voids resting over a nonlocal elastic solid half-space with voids has been studied. Dispersion relations are derived using appropriate boundary conditions of the model. It is found that there exist two fronts of Love-type surface waves that may travel with distinct speeds. The appearance of the second front is purely due to the presence of voids in layered media. Both fronts are found to be dispersive in nature and affected by the presence of the nonlocality parameter. The first front is found to be nonattenuating, independent of void parameters and analogous to the Love wave of classical elasticity, while the second front is attenuating and depends on the presence of void parameters. Each of the fronts is found to face a critical frequency above which it ceases to propagate. For a specific model, the variation of the phase speeds of both the fronts with frequency, nonlocality, voids and thickness parameters is shown graphically. Attenuation coefficient versus frequency for the second front has also been depicted separately. Some particular cases are deduced from the present formulation.